The effect of total factor productivity on the food security and livelihood vulnerability of farm households in Bangladesh - Sarma, Paresh Kumar; Alam, Mohammad Jahangir; Begum, Ismat Ara; McKenzie, Andrew M. (Frontiers in Sustainable Food Systems, 2024)
Food security and livelihood vulnerability are important issues for the economic sustainability of developing countries like Bangladesh. This study examines the influence of total factor productivity (TFP) on the livelihood vulnerability and food security of rice farming households in Bangladesh. Data from 1,841 rice farming households were extracted from the Bangladesh Integrated Household Survey (2015 and 2018) conducted by the International Food Policy Research Institute. Various statistical methods, such as the stochastic frontier model, principal component analysis, path analysis using structural equation modeling, and multivariate regression, were employed to analyze the data. The study utilizes a multivariate modeling approach that combines the stochastic frontier model to determine TFP and sophisticated methodologies to estimate the livelihood vulnerability index (LVI) and women's empowerment Integrated Household Survey (2015 and 2018) administered by the International Food Policy Research Institute (IFPRI). The stochastic frontier model, principal component analysis, path analysis using structural equation modeling, and multivariate regression were used to analyze the data. The overall scores were 0.454, 10.72, 0.703, and 0.717 for the livelihood vulnerability index, household dietary diversity, TFP, and the women's empowerment in agriculture index (WEAI), respectively. The multivariate regression analysis results revealed that TFP, the household wealth index, the WEAI, per capita food expenditure, household-level welfare, and household size have a significant positive impact on the household dietary diversity score. In contrast, the livelihood vulnerability index is significantly negatively influenced by TFP, per capita food expenditure, and household size. This means that if TFP increases, farmers' livelihood vulnerability decreases, and their household food security increases. Accordingly, increasing TFP should be considered when designing policies aiming to meet the United Nations Sustainable Development Goal 2.